Effectiveness of Village Fund Management in Physical Development in Keruak District - Arfizi Mita Raga Seprian; Wirawan Suhaedi; L. Takdir Jumaidi (Socio-Economic and Humanistic Aspects for Township and Industry, 2023)
The aim of this research is to determine the effectiveness of village fund management in physical development in Keruak District and the role of village funds in village programs. This research is quantitative descriptive research. The results of this research show that the effectiveness of village fund management for physical development in Keruak District in 2021 and 2022 is in the effective category with average percentages in 2021 and 2022 of 100% and 93% respectively. In the 2021 and 2022 budget years, the percentage portion of village funds for physical development to total village funds is on average 29% and 14%, to total physical development funds is 100% and 93%, and to total village income is 20% and 10%. Meanwhile, the portion of village funds for social activities in total village funds is on average 57.74% and 80.08%; the total funds for social activities for the two budget years are the same, namely 100%; and to total village income of 39% and 55%. In the economic sector, it was found that Keruak District has a budget only for 2021 in the form of BUMDes capital participation. The share of village funds for economic activities in total village funds, total economic activity funds, and total village income in 2021 will be 3%, 47%, and 2% respectively.